The evolutionary status of the white dwarf companion of the binary pulsar PSR J1713+0747 - Benvenuto, Omar Gustavo (2006)
Recently Splaver et al. have measured the masses of the white dwarf and the neutron star (NS) components of the PSR J1713+0747 binary system pair by means of the general relativistic effect known as Shapiro delay with very high accuracy. Employing these data we attempt to find the original configuration that evolved to the observed system. For this purpose we perform a set of binary evolution calculations trying to simultaneously account for the masses of both stars and the orbital period. In doing so, we considered normal (donor) stars with an initial mass of 1.5M ⊙, while for the neutron star companion we assumed a mass of 1.4M ⊙. We assumed two metallicity values for the donor star (Z = 0.010 and 0.020) and that the initial orbital period was nearly 3 d. In order to get a good agreement between the masses of the models and observations we had to assume that the NS is only able to retain ≲0.10 of the matter transferred by the donor star. Calculations were performed employing the binary hydro code developed by Benvenuto & De Vito, that handles the mass transfer rate in a fully implicit way together with state-of-the-art physical ingredients and diffusion processes. Now our code also includes a detailed non-grey treatment for the atmospheres of white dwarfs (WDs). We compare the structure of the resulting WDs with the characteristic age of PSR J1713+0747 finding a nice agreement with observations by Lundgren et al. especially for the case of a donor star with Z = 0.010. This result indicates that, at least for the purposes of this paper, the evolution of this kind of binary system is fairly well understood. The models predict that, due to diffusion, the atmosphere of the white dwarf is an almost hydrogen-pure one. We find that such structures are unable to account for the colours measured by Lundgren et al. within their error bars. Thus, in spite of the very good agreement of the model with the main characteristics of the system, we find that some discrepancies in the WD emergent radiation remain to be explained.